New triterpenoids from Leonurus japonicus (Lamiaceae). (February 2019) - Zhou, Qin-Mei; Zhu, Huan; Feng, Rui; Peng, Cheng; Yang, Huai; Liu, Fei; Wang, Ya-Nan; Xiong, Liang
Abstract: Three new triterpenoids (1, 4, and5 ), together with 17 known analogues, were isolated from the ethyl acetate soluble portion of the EtOH extract of Leonurus japonicus Houtt. Their structures were determined by spectroscopic analysis. All known triterpenoids were isolated from the genus Leonurus for the first time. Among them, triterpenoids2 –3, 9 –12, and16 –20 were first isolated from the family Lamiaceae. Furthermore, the cycloartane, taraxastane, ursane, lupane, euphane, and dammarane types are reported here for the first time from the genus Leonurus . Highlights: Three new triterpenoids were isolated from Leonurus japonicus. All known triterpenoids were isolated from the genus Leonurus for the first time. Six types of triterpenoids are reported for the first time from the genus Leonurus.